An efficient harvesting strategy for agarwood based on the correlation analysis of resin formation and leaves dynamic changes induced by integrated induction method - Jie Chen; Tianyu Gao; Yanhui Ge; Xiaodong Chen; Meirou Feng; Xiaoying Chen; Weimin Zhang; Xiaoxia Gao (PLoS ONE, 2025)
Agarwood is a resin produced by wounded Aquilaria plants. Aquilaria sinensis (Lour.) Gilg  is the original plant source of agarwood in China. Formic acid combined with Botryosphaeria rhodina A13 (FAA13) induces the formation of artificial agarwood as an effective integrated induction method. However, its formation mechanism is still unclear, and the harvesting time of agarwood has not been elucidated. In this work, we analyzed FAA13-induced artificial agarwood and leaves at different time points within one year based on endophytic fungal community, expression of related genes, and secondary metabolites. The induction process by FAA13 was divided into two stages. In agarwood, we found that fungal diversity and relative abundance decreased in stage 1 but increased in stage 2. Additionally, genes related to 2-(2-phenylethyl) chromones synthesis were mainly expressed in stage 1, while those related to sesquiterpene synthesis were mainly expressed in stage 2. The primary differential metabolites between the two stages were the content of ethanol-soluble extractives (EEC%) in the agarwood and epi-friedelinol and friedelin in the leaves. EEC% in agarwood stabilized and was at a high level in stage 2. At the same time, we observed friedelin rose rapidly from a plateau or after a slight decline, and epi-friedelinol continued to rise. We found similar results in artificial agarwood induced by combining formic acid with Fusarium sp. A2 (FAA2). The content of epi-friedelinol and friedelin in leaves can be used as an index to judge agarwood’s harvesting period during the integrated method’s induction process. The appropriate harvesting period for agarwood should be determined by collecting leaves in stage 2 (8 months later) without damaging the tree and assessing whether friedelin enters a rapid rise from the plateau stage by rapidly determining epi- friedlinol and friedelin content.